Structure and biological activities of eumenine mastoparan-AF (EMP-AF), a new mast cell degranulating peptide in the venom of the solitary wasp (Anterhynchium flavomarginatum micado) - Konno, K.; Hisada, M.; Naoki, H.; Itagaki, Y.; Kawai, N.; Miwa, A.; Yasuhara, T.; Morimoto, Y.; Nakata, Y. (Elsevier B.V., 2000)
A new mast cell degranulating peptide, eumenine mastoparan-AF (EMP-AF), was isolated from the venom of the solitary wasp Anterhynchium flavomarginatum micado, the most common eumenine wasp found in Japan. The structure was analyzed by FAB-MS/MS together with Edman degradation, which was corroborated by solid-phase synthesis. The sequence of EMP-AF, Ile-Asn-Leu-Leu-Lys-Ile-Ala-Lys-Gly-Ile-lle-Lys-Ser-Leu-NH(2), was similar to that of mastoparan, a mast cell degranulating peptide from a hornet venom; tetradecapeptide with C-terminus amidated and rich in hydrophobic and basic amino acids. In fact, EMP-AF exhibited similar activity to mastoparan in stimulating degranulation from rat peritoneal mast cells and RBL-2H3 cells. It also showed significant hemolytic activity in human erythrocytes. Therefore, this is the first example that a mast cell degranulating peptide is found in the solitary wasp venom. Besides the degranulation and hemolytic activity, EMP-AF also affects on neuromuscular transmission in the lobster walking leg preparation. Three analogs EMP-AF-1 similar to 3 were snythesized and biologically tested together with EMP-AF, resulting in the importance of the C-terminal amide structure for biological activities. (C) 2000 Elsevier B.V. Ltd. All rights reserved.